Decapod crustaceans from the state of Ceará, northeastern Brazil: an updated checklist of marine and estuarine species, with 23 new records - Pachelle, Paulo P.g.; Anker, Arthur; Mendes, Cecili B.; Bezerra, Luis E.a. (Zootaxa, 2016)
The present study is the first major assessment of the marine decapod fauna of Ceará, northeastern Brazil, since contributions of J. Fausto-Filho in the 1960s–1970s. A fully updated checklist of all decapod crustaceans occurring in marine and estuarine habitats of Ceará is provided, based on literature records, specimens held in two carcinological collections of the Universidade Federal do Ceará (UFC), and material collected mainly by the authors between 2011 and 2014. A total of 337 decapod species are listed, distributed among the following taxa: Achelata (8 species), Anomura (42 species), Astacidea (1 species), Axiidea (11 species), Brachyura (162 species), Caridea (83 species), Dendrobranchiata (20 species), Gebiidea (9 species), and Stenopodidea (1 species). Among them, 23 species represent new records for Ceará, with 14 species, viz. Alpheus peasei (Armstrong, 1940), A. thomasi Hendrix & Gore, 1973, Ambidexter symmetricus Manning & Chace, 1971, Axianassa australis Rodrigues & Shimizu, 1992, Biffarius biformis (Biffar, 1971), B. fragilis (Biffar, 1970), Leptalpheus axianassae Dworschak & Coelho, 1999, L. forceps Williams, 1965, Lysmata bahia Rhyne & Lin, 2006, L. intermedia (Kingsley, 1878), Merhippolyte americana Holthuis, 1961, Neocallichirus maryae Karasawa, 2004, Ogyrides hayi Williams, 1981, and Typton carneus Holthuis, 1951, now having Ceará as the northern-most limit in their distribution range along the Brazilian coastline. One shrimp species, Lysmata lipkei Okuno & Fiedler, 2010, which was also found in the state of Rio Grande do Norte, possibly represents an invasive taxon in Brazil and the western Atlantic, originating from the Indo-West Pacific. Alpheus buckupi Almeida, Terossi, Araújo-Silva & Mantelatto, 2013, previously recorded from Ceará based on a colour photograph, is confirmed from this state, with specimens from several new localities. A few doubtful records from Ceará are briefly discussed. Colour photographs are provided for most of the taxa newly recorded from Ceará; some species are illustrated in colour for the first time.